The Evaluation of the TOEFL Preparation Program in an Indonesian University - Setiyorini, Tri Jampi (Institut Agama Islam Negeri Palopo, 2025)
Many university learners from non-English department have difficulties during the TOEFL preparation program. This research aims to evaluate the implementation of the TOEFL preparation program in an Indonesian University based on context, input, process, and product. The research participants were a TOEFL instructor and 121 management students in the seventh semester. This research was evaluation research. The research instruments were online observation, checklist, and one-on-one interview. The results indicated that the TOEFL preparation program had not fulfilled the context because there was no curriculum in the TOEFL preparation program. Then, the input was good because the instructor used the structured lesson plan, the TOEFL books, the TOEFL software, structured schedule, qualified human resource, and clear budget. The process was moderate because the instructor could explain the materials clearly, gave questions-answers and exercises to check students’ understanding of the material, but he still used teacher-centred learning. The product was in low category. Most students’ TOEFL scores were under 400. The researcher suggests that the instructor designs the TOEFL curriculum, uses student-centred learning, encourage learners to participate actively in the class, uses team teaching, emphasize vocabulary, and give more exercises to improve the quality of the TOEFL preparation program.